The Tradition of Kissing Kyai's Hand: A Case Study at Islamic Boarding School of Raudlatul Hidayah Sulusuban Central Lampung - Fajar Hari Nugroho; Anwar Mahmudi; Tursila Tursila; Mispani Mispani; Jaenullah Jaenullah; Ernawati Ernawati (Journal of Research in Islamic Education, 2021)
This research was conducted at the Raudlatul Hidayah Islamic Boarding School, Sulsuban, Seputih Agung Central lampung. The greeting by kissing kyai’s hand for the santri has its own meanings, it is not just a mere habit but also expecting the blessing of a kyai or teacher in studying. It also includes moral education, because kissing the kyai's or teacher's hand is an act of greeting form of respect for a kyai. This research is a case study where the data were obtained through interviews and observations towards the santri , the kyai and the interections of santri and kyai at Raudhotul Hidayah Islamic Boarding School, Sulsuban, Seputih Agung, Central Lampung. The data analyzed interactively inorder to obtained required data. The results of this study found that the tradition of shaking hands and kissing the Kyai's hand was a symbol or form of ta'dzim of the santri to the kyai and in order to obtain useful knowledge.